Effects of Maternal Protein Supplementation at Mid-Gestation of Cows on Intake, Digestibility, and Feeding Behavior of the Offspring (2022)
: It is well known that intrauterine growth-restricted offspring present physiologic and metabolic modifications later in life. Therefore, understanding the impact of the maternal nutritional plane on feed intake patterns may lead to new feeding strategies to improve the feed efficiency and performance of beef cattle. In this study, we have evaluated the effect of maternal protein supplementation (PS) during mid-gestation and its interaction with the offspring’s sex on the voluntary feed intake and nutrient use of the progeny. Our results show that PS during midgestation increases performance and improves the voluntary feed intake of the offspring. Prenatal PS induced favorable changes in the feeding behavior, in which CON offspring spent more time per day eating supplements and ruminating but spent fewer periods in idleness. Maternal protein restriction demonstrated positive effects on the ability to digest the nutrients of male calves. In summary, our data show that PS alters the gain potential, indirectly demonstrating an increase in their nutritional requirements. In contrast, protein restriction causes a compensatory mechanism on the offspring’s nutrient useability in a sex-dependent manner, increasing the total tract digestibility of nutrients in response to a growth-restriction exposure during intrauterine development